Reformulasi Ketentuan Eksekusi Jaminan Fidusia dan Relevansinya dengan Pemenuhan Prinsip Keadilan, Kemanfaatan dan Kepastian Hukum - Hasanuddin Muhammadin; M. Yasin Al Arif (University of Udayana, 2023)
This paper is a normative research that tries to decipher the differences regarding changes to the provisions of the execution of fiduciary guarantees after the decision of the Constitutional Court. The debate is based on the opinion that the Constitutional Court's decision changes the characteristics of executing fiduciary guarantees to become more complicated because it costs more and takes a longer time. The data source for this paper is in the form of Constitutional Court Decisions and laws and regulations. The author uses interpretation techniques to examine and analyze the problems in this article. As a result, the reformulation of the provisions on the execution of fiduciary guarantees carried out by the Constitutional Court is by the principles of justice, benefit, and legal certainty. The Constitutional Court has determined that the execution of a fiduciary guarantee object can only held if there is an agreement regarding the breach of contract and there is a willingness to surrender the fiduciary guarantee. They are regulated so that debtors are not treated arbitrarily by creditors. The decision provides options to maximize simple lawsuits and utilize electronic court and trial administration. Tulisan ini merupakan penelitian normatif yang mencoba menguraikan perbedatan mengenai perubahan ketentuan eksekusi jaminan fidusia pasca putusan Mahkamah Konstitusi. Perdebatan tersebut didasarkan pada pendapat bahwa putusan Mahkamah Konstitusi mengubah karakteristik eksekusi jaminan fidusia menjadi lebih rumit karena mengeluarkan biaya lebih besar dan waktu yang lebih lama. Sumber data tulisan ini berupa Putusan Mahkama Konsitusi maupun peraturan perundang-undangan. Penulis menggunakan teknik interpretasi untuk menalaah dan menganalisa masalah dalam artikel ini. Hasilnya reformulasi ketentuan eksekusi jaminan fidusia yang dilakukan oleh Mahkamah Konsitusi sudah sesuai dengan prinsip keadilan, kemanfaatan dan kepasatian hukum. Mahkamah Konsitusi telah menetapkan bahwa eksekusi objek jaminan fidusia hanya dapat dilakukan apabila ada kesepakatan mengenai cidera janji dan ada kerelaan menyerahkan jaminan fidusia. Hal ini diatur agar Debitur agar tidak diperlakukan secara sewenang-wenang oleh Kreditur. Putusan tersebut memberi pilihan untuk memaksimalkan gugatan sederhana dan memanfaatkan administrasi perkaran dan persidangan secara elektronik.